Optimization of coil baking parameters using design of experiments - Phantasak Punnarungsri (2018)
Hard disk drives are a crucial component for data storage computers. One of the important tools in a hard disk drive is the hard disk actuator which influenced the drive quality. The hard disk actuator main component was a coil attached to an actuator arm. The coil quality has direct effect on the hard disk drive's performance. At present, the study found that the companies that manufactured hard disk drive actuator faced problems in coil production. One of the problems occurred during the coil baking procedure because there was no proper parameters set for the oven. Therefore, the coil transformed or swelled and led to wrong sizes. The purposes of this research were to seek for the best coil baking parameters and analyze other factors affecting coil baking. The research applied experimental design methodology to find the most optimal parameters. The research utilized three-level factorial design considering 4 factors with 3 levels of factors. The experiment then measured the difference of coil thickness before and after the baking. The control factors were baking durations, baking temperatures, coil positions in the oven, and the pressure levels of the oven air duct. The research found that all factors affected the coil baking. The optimal parameters were at baking duration of 6 hours, oven temperature at 175 oC, middle level in the oven and low level air duct pressure.